Practitioner Profile: An Interview with Susan Bross, AFC® - Susan Bross (Journal of Financial Therapy, 2011)
Susan Bross is a nationally accredited financial counselor who established her private practice in 1992. She currently lives in San Rafael, California. She brings a multi-faceted background and a combination of skills to her work. As a financial counselor, she works with individuals, couples, and entrepreneurs throughout the nation to help clients develop a practical and emotionally healthy relationship with money. When asked, she will tell you that she is passionate about her work because it mirrors her own hard-won path with money. Readers of the Journal will find Ms. Bross’s approach to financial therapy inspiring. She teaches simple tools for effortless and sustainable cash flow and money management. She also guides her clients to balanced attitudes and beliefs about money and success.
Keywords: Bross; Financial Counseling